Application of thermal imaging for prediction soil saturation for slope monitoring - Mohamad Hazman, Mohamad Yusof (2017)
Landslide can cause human injury, loss of life and economical problem. One of the factors is due to the heavy rain. Hence, to overcome this problem, this study investigates a new method to detect spots of high water saturation which is integrated with a thermal camera system to provide early detection of landslide. This study examines the usage of thermal camera on slopes at hillside at Jalan Gambang for prediction of soil saturation of the soil. The thermal camera is selected because it provides accurate predict where landslide going to occur. Various soil properties were studied, including specific gravity, Atterberg limits, swell index and organic matter content. The soil-water characteristic curve (SWCC) of soil sample were also determined. Experimental results demonstrated that the results obtained are able to determine the point of soil that starts to saturate and from the thermal imaging, the image of the saturated soil will be in blue colour with range of water content stated for each image. From the observation, this technique is quite accurate but still has their weakness and error.